Attaining expertise in regional anaesthesia training using a multifactorial approach incorporating deliberate practice - McLeod, Graeme; Chuan, Alwin; McKendrick, Mel (British journal of anaesthesia : BJA, 2024)
The most effective way of delivering regional anaesthesia training and the best means of demonstrating competency have not been established. Clinical competency, based on the Dreyfus and Dreyfus lexicon, appears unachievable using current training approaches. Lessons should be taken from the worlds of music, chess, and sports. Modern skills training programmes should be built on an explicit and detailed understanding with measurement of a variety of factors such as perception, attention, psychomotor and visuospatial function, and kinesthetics, coupled with quantitative, accurate, and reliable measurement of performance.